Research on High-quality development of enterprises based on an intelligent background - Gao, Yuhao (Transactions on Economics, Business and Management Research, 2024)
In the global economy, intelligent technology has attracted much attention as a crucial factor in propelling enterprises towards achieving high-quality development growth. Taking the financial reports of A-share listed companies in Shanghai and Shenzhen Stock exchanges published from 2007 to 2022 as samples, this study explores the influence and mechanism of intelligent technology on the high-quality development of enterprises. The study finds that intelligent technology has a substantial positive impact on enhancing the high-quality growth of businesses, especially by improving innovation efficiency and management efficiency. In addition, digital inclusive finance and the digital economy have a positive moderating effect on the relationship between intelligent technology and the high-quality development of enterprises. These results offer practical backing for the advancement of corporate intelligence and establish a vital theoretical and empirical foundation for companies to uphold their competitive edge in an intensely competitive market landscape.